PENERAPAN SAK ETAP PADA PENYUSUNAN LAPORAN KEUANGAN - Sumitri .; Natalia Titik Wiyani (Akademi Akuntansi YKPN Yogyakarta, 2017)
The financial report is a form of responsibility for the management of the company by themanagement to internal and external parties. The financial statements should be prepared based onthe applicable standards that can be described with the concepts and the same understanding by eachuser. To overcome the difficulties experienced by the perpetrators of the SME business, made specificstandards for entities without public accountability, called SAK ETAP. This study aims to determinethe application of accounting conducted by PD.Tio Jaya Bekasi regency in running the business. PD.Tio Jaya is a business engaged in the production and sale of the brains of fish and fish nuggets. Themethod used in this research is a comparative descriptive. The results based on observations made todetermine the recording made by PD.Tio Jaya during the month of December 2014, shows that thecompany does not make financial reports. This study suggested that PD.Tio Jaya not only did therecording but also prepare financial statements in accordance with GAAP ETAP.Keyword : financial statement, financial accounting standard entity without public accountability(SAK ETAP)